Emotions, Positionalities and the Reproduction of Border Regimes: Multi-Sited Ethnography with Syrian Transnational Families - Miriam Stock (Nordic Journal of Migration Research)
This article analyses how overlapping border regimes between Europe and the Middle East affect and shape the emotions of Syrian migrants and their left-behind families and communities. It argues, from a transnational perspective, that border regimes are always emotional regimes. This research combines different research strands, including one on border regimes, with a theoretical discussion on emotions in migration and transnational contexts. The empirical material is based on a multi-sited ethnography of young men in transnational Syrian families in Germany, Lebanon and Syria. My analysis indicates the omnipresence of different emotions, such as envy and guilt, which form different subjectivations and link different positionalities in overlapping border regimes between the Middle East and Europe. Finally, my mixed feelings as a Germany-based researcher are also considered. I show how these emotions and subsequent subjectivations have a direct impact on transnational relations and positionalities in overlapping border regimes and argue for more sensitivity towards emotions in research on such regimes.